2020
DOI: 10.1186/s42834-020-00063-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the adsorption capacity of acetaminophen on sugarcane bagasse and corn cob by dynamic simulation

Abstract: Acetaminophen (ACT), an antipyretic analgesic, is one of the emerging pollutants that has been found in high concentrations in domestic and hospital wastewaters. This study 7the adsorption capacity of sugarcane bagasse (SB) and corn cob (CC) for the ACT removal through the dynamic simulation of the adsorption column using Aspen Adsorption® V10. The effects of flow rate (1.5–3.0 mL min− 1), ACT initial concentration (40–80 mg L− 1), and bed height (20–35 cm) on the breakthrough curves were studied. Finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…From Table 7 as the breakthrough time increases for Study A, B and C, when the h increases from 0.25 m to 1 m. This is because when the h increases, the number of biosorbent particles within the bed column increases, as well as the total surface area and the number of active sites available for adsorption of Pb (II) ions also increases (Juela, 2020), which leads to the increased amount of Pb (II) ions being adsorbed. Since Co ions is keep constant, the present of more biosorbent particles increases the breakthrough time of the bed column as shown in Figure 3.…”
Section: Effect Of Bed Heightmentioning
confidence: 91%
See 3 more Smart Citations
“…From Table 7 as the breakthrough time increases for Study A, B and C, when the h increases from 0.25 m to 1 m. This is because when the h increases, the number of biosorbent particles within the bed column increases, as well as the total surface area and the number of active sites available for adsorption of Pb (II) ions also increases (Juela, 2020), which leads to the increased amount of Pb (II) ions being adsorbed. Since Co ions is keep constant, the present of more biosorbent particles increases the breakthrough time of the bed column as shown in Figure 3.…”
Section: Effect Of Bed Heightmentioning
confidence: 91%
“…The interparticle voidage is needed in the bed configuration during the simulation in Aspen Adsorption and was calculated based on Equation 3 (Nieva et al, 2019). For Table 3, as water was used as solvent for all the studies, the association factor of solvent for water is 2.26 and the molecular weight of the water is 18.01 g/mol (Juela, 2020). The dynamic viscosity of the solvent is assumed to be the same as the dynamic viscosity of the solution and both are assumed to be the same as the dynamic viscosity of the water at respective temperature (Wright State University, 2022).…”
Section: Materials and Apparatusmentioning
confidence: 99%
See 2 more Smart Citations
“…Although various adsorbents have been applied for the uptake of pollutants ranging from biochar's, zeolites, clay, etc., the activated carbon has however been found to be an effective adsorbent for the uptake of inorganic and organic micropollutants [9]. Low-cost materials have also been extensively studied as alternative adsorbents for pharmaceuticals and recent studies have shown that banana stalk [10], corn cob and sugarcane bagasse [11], rice husk [12], argan tree nutshell [13], etc. could be used effectively as adsorbents.…”
Section: Introductionmentioning
confidence: 99%